Keterkaitan Budaya Organisasi, Komunikasi dan Manajemen Karir - Tri Bastuti Purwantini; Puji Astuti; Nur Insan; Suparno Suparno; Puri Noviarti (Diversity: Jurnal Ilmiah Pascasarjana, 2022)
Organizational culture is an organizational model that regulates values and norms, while communication contains cultural values. These two variables are interrelated and affect individual activities and career success in an organization. This study aims to analyze the relationship between culture, communication, and career management. The method is a literature study with information data analysis using qualitative descriptive analysis. The results showed that culture and communication have a positive reciprocal relationship. Culture affects communication and conversely, communication affects culture. This means that communication and culture are interconnected concepts. Between cultural variables, communication within the organization will synergize in developing work activities to achieve career success and support organizational goals. Organizational communication culture and work motivation simultaneously affect employee performance. Meanwhile, organizational culture and career development simultaneously affect employee performance. The better the organizational culture, the better the employee's performance, and vice versa. The influence of career development variables on employee performance is positive, if career development increases, employee performance will increase, and vice versa. Therefore, improving employee performance can be influenced by culture and career development. Thus competence and an effective communication model with strong organizational culture can improve employee performance and success and expected to support organizational goals.